Traditional Chinese Medicine in Java - Risty Fahira Nurhalisa; Nindita Swasti Lituhayu; Rudiansyah Rudiansyah (International Journal of Chinese Interdisciplinary Studies, 2024)
Before Western health science came to Indonesia, people had long used indigenous or traditional medicine. Traditional Chinese medicine is also one of the conventional medicines in Indonesia, which is a legacy of treatment from other countries and is developing very rapidly, so in its development; traditional medicine is popular in Indonesia, including in the cities of Java. This research aims to see how traditional Chinese medicine has developed in Java. This paper was written using methods and rules in historical science. The first stage is "heuristics" or data collection. Traditional medicine's approach is more holistic (comprehensive), while conventional treatment's approach is symptomatic (therapy focuses on the symptoms that arise). Generally, the regulations and services for traditional medicine in Indonesia are clear because they have been regulated in legislation and Governor Regulations for provincial areas.